Development and validation of an asthma self-knowledge questionnaire - Adalberto Fernandes Dos Santos; Renata Costa; Henrique Pereira; Ana Rita Pedro; Luis Taborda-Barata (PLoS ONE, 2025)
Background Validated questionnaires for adequately assessing knowledge about asthma are scarce. Thus, the primary objective of the present study was to develop and validate an asthma self-knowledge questionnaire, based on international recommendations on the disease. The secondary objectives were to compare knowledge about asthma between asthmatic patients and non-asthmatic individuals; assessing whether asthma affects the level of self-knowledge of the disease and what factors may be associated with poorer self-knowledge of the disease. Methods The Bronchial Asthma Self-Knowledge Questionnaire was developed, and validation studies were performed: logical or apparent validity, content validity, construct validity; internal consistency (Cronbach’s alpha test), test-retest or reproducibility, in a face-to-face survey with 104 asthmatic patients and 131 non-asthmatic individuals (n = 235). Other questionnaires were also applied: Mini Mental State Examination (in individuals over 65 years of age), Depression Scales (CES-D for individuals under 65 and GDS for individuals over 65 years of age), Demographic Questionnaire, Health Literacy, and the Characterization Questionnaire for bronchial asthma. Results Regarding development of the questionnaire, content validity, determined using I-CVI allowed reducing the questionnaire to 21 items. The test proved to have an acceptable value of in-ternal consistency and the data were considered as normally distributed; the questionnaire presented good temporal stability, by test-retest, although Spearman rho values were significantly stronger in the asthmatic group. Finally, confirmatory factorial analysis yielded acceptable values for PCFI and PGFI, as well as a satisfactory value for RMSEA. In terms of the application of the questionnaire, both groups under study (asthmatics and non-asthmatics) showed statistically significant differences in replies of self-knowledge questionnaire items. Finally, factors such as health literacy disturbances seem to marginally influence self-knowledge of bronchial asthma. Conclusions The developed and validated questionnaire showed adequate psychometric robustness. In terms of construct validity, by known group (bronchial asthma) validity, the test was able to discriminate between patients with asthma and participants without asthma, regarding self-knowledge of the disease.